PENGARUH PENGHINDARAN PAJAK (TAX AVOIDANCE), MANAJEMEN LABA, DAN KEPEMILIKAN MANAJERIAL TERHADAP BIAYA HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (2016-2019) - Tivani Kinait; Sri Ayem (Universitas Muhammadiyah Makassar, 2021)
This study aims to examine the effect of tax avoidance (tax avoidance), earnings management, and managerial ownership on the cost of debt. The population used in this study is manufactures that have been listed on the Indonesia Stock Exchange (IDX) in 2016-2019. The research sample was taken with the object of manufacturing companies during 2016-2019, based on the purposive sampling method obtained by 20 manufacturing companies or 80 annual financial reports. The data used is secondary data in the form of company's annual financial reports obtained from the Indonesia Stock Exchange (IDX). Data analysis techniques in this study are descriptive statistics, classical assumption test and multiple linear regression test. The software used is SPSS 23. The test results of this study use multiple linear regression analysis. The results show that tax avoidance has a positive effect on the cost of debt. Earnings management has a positive effect on the cost of debt. Managerial ownership has a negative effect on the cost of debt.